Modeling and Optimization of WaterâFoodâEnergy Nexus for Malaysiaâs Agricultural Sector - Siah, Q. (MDPI, 2022)
The waterâfoodâenergy (WFE) nexus is a strategic system that integrates different separated sectors by using their interconnectedness to reduce trade-offs and allow sustainable development by preventing future resource insecurity. Traditionally, the water, energy, and food sectors operate indi-vidually and result in different challenges such as resource scarcity, conflicts in the uses of upstream and downstream hydro systems, and power supply crises due to serious water pollution. Reports so far have only implemented the WFE nexus in countries and cities outside of Malaysia. In addition, there is yet to be a model in literature revolving only on optimizing the agricultural sectorâs resources distribution. Hence, this paper aims to develop the first systematic and integrated model for optimal planning of resource allocation in Malaysiaâs agricultural sector. The novelty and contribution of this research could be concluded as: (1) multi-objective planning incorporating economic and environmental factors such as economic benefits and carbon emission limit, (2) focusing on the agricultural sector considering geologically-specific crops, livestock, and residents, (3) considering the potential waste recycle systems including wastewater treatment and biomass treatment. The superstructure framework developed based on the case study in Perak, Malaysia aids the implementation of the WFE nexus system locally where trade-offs and synergies between the different sub-units are modelled. From the results, it can be concluded that irrigated paddy crops could contribute to a higher profit compared to palm oil and rubber crops. Thus, future development can be focused on irrigated paddy crops while meeting other constraints and demands to ensure the resources are optimally utilized. The multi-objective optimization solved using MINIMAX algorithm also provides decision-makers with a guideline on how to implement WFE nexus locally in the agricultural sector. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.